2013
DOI: 10.1109/toh.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Configuration-Based Optimization for Six Degree-of-Freedom Haptic Rendering for Fine Manipulation

Abstract: Six-degree-of-freedom (6-DOF) haptic rendering for fine manipulation in narrow space is a challenging topic because of frequent constraint changes caused by small tool movement and the requirement to preserve the feel of fine-features of objects. In this paper, we introduce a configuration-based constrained optimization method for solving this rendering problem. We represent an object using a hierarchy of spheres, i.e., a sphere tree, which allows faster detection of multiple contacts/collisions among objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…For accurate collision response, a configuration-based optimization method [23] is used to compute a non-penetrated configuration for the graphic tool contacting the deformed objects, and to compute the six-dimensional force/torque response to the haptic tool.…”
Section: Overview Of Our 6-dof Haptic Rendering Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For accurate collision response, a configuration-based optimization method [23] is used to compute a non-penetrated configuration for the graphic tool contacting the deformed objects, and to compute the six-dimensional force/torque response to the haptic tool.…”
Section: Overview Of Our 6-dof Haptic Rendering Methodsmentioning
confidence: 99%
“…In this approach, the avatar of the haptic device, which we call the haptic tool, and its graphic display, which we call the graphic tool, are treated separately. The constraint-based approach aims to constrain the pose of the graphic tool to be free of penetration, while the haptic tool can penetrate into objects [23]. Duriez et al introduced a constraint-based method for simulation of deformation due to contacts [4], [5].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Constrained dynamics is not a novel problem to computational haptics, as it is a corner stone for accurate and robust simulation of frictional contact [4], [11], [16], [19], [12]. However, we have observed that typical solvers for contact constraints do not work well with the deformation constraints of nonlinear skin.…”
Section: Introductionmentioning
confidence: 98%